Knowledge and Attitude of Mothers toward Preschool Sexual Education - K Mobredi; SB Hasanpoor Azgahdy; L Amiri Farahani (Iran University of Medical Sciences, 2017)
Abstract Background & Aims: Sex education is one of the most difficult and most sensitive types of education. Meanwhile, parents' knowledge and attitudes, especially mothers, has the most important role in the education of healthy sexual behavior to children in pre-school. For this purpose, this study was conducted to evaluate knowledge and attitude of mothers towards preschool sex education. Materials & Methods: In this descriptive study, 200 mothers of preschoolers were selected from health centers under the affiliation of Iran University of Medical Sciences, using multi-stage random sampling. Data were collected by valid and reliable self-administered questionnaires through self-report. Then data were analyzed, using SPSS software (v.23) and frequency tables. Results: The results of this study showed that the mean score of mothers' knowledge was 28.56 ± 4.04 (Range: 0-40) and the mean score of attitude was 49.85 ± 7.45 (Range: 15-75) that represents the average knowledge and attitude of mothers. There was a significant relationship between attitudes and educational level (P > 0.001). Conclusion: Given the mothers' average knowledge and attitude towards pre-school sex education, it seems necessary to develop appropriate educational contents and strategies to increase mothers' knowledge and attitude.